2015
DOI: 10.1080/15226514.2015.1131235
|View full text |Cite
|
Sign up to set email alerts
|

Mixed planting with a leguminous plant outperforms bacteria in promoting growth of a metal remediating plant through histidine synthesis

Abstract: The effectiveness of plant growth promoting bacteria (PGPB) in improving metal phytoremediation is still limited by stunted plant growth under high soil metal concentrations. Meanwhile, mixed planting with leguminous plants is known to improve yield in nutrient deficient soils but the use of a metal tolerant legume to enhance metal tolerance of a phytoremediator has not been explored. We compared the use of Pseudomonas brassicacearum, Rhizobium leguminosarum, and the metal tolerant leguminous plant Vicia sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Histidine is an essential amino acid with a positively charged imidazole functional group (Chakrabarti, 1990;Gluster, 1991;Gramlich et al, 2013). The occurrence of Zn histidine in the roots in the ZnSO4 treatments in the present study agrees with previous studies of Zn hyperaccumulator species (Adediran et al, 2016b;Lasat et al, 1998;Salt et al, 1999). Metal tolerance and hyperaccumulation via histidine complexation has been demonstrated in studies involving Ni (Salt et al 1999) and histidine has been implicated in Cu and Zn toxicity responses (Sharma and Dietz, 2006).…”
Section: Xas Analysis Of Zn Speciation and Distribution In Roots And ...supporting
confidence: 90%
See 2 more Smart Citations
“…Histidine is an essential amino acid with a positively charged imidazole functional group (Chakrabarti, 1990;Gluster, 1991;Gramlich et al, 2013). The occurrence of Zn histidine in the roots in the ZnSO4 treatments in the present study agrees with previous studies of Zn hyperaccumulator species (Adediran et al, 2016b;Lasat et al, 1998;Salt et al, 1999). Metal tolerance and hyperaccumulation via histidine complexation has been demonstrated in studies involving Ni (Salt et al 1999) and histidine has been implicated in Cu and Zn toxicity responses (Sharma and Dietz, 2006).…”
Section: Xas Analysis Of Zn Speciation and Distribution In Roots And ...supporting
confidence: 90%
“…We found higher proportions of Zn histidine complexes in roots than in the bulk and rhizospheric soils, where the proportions were approximately equal. Therefore, like phytate, we interpret the observed gradient as reflecting histidine production in the form of root exudates (see also Adediran et al, 2016b) but with long range transport into the rhizospheric and bulk soil.…”
Section: Xas Analysis Of Zn Speciation and Distribution In Roots And ...mentioning
confidence: 78%
See 1 more Smart Citation
“…Zn−histidine has been reported in previous studies and is thought to help reduce the toxicity of Zn to the plant, 8,41,65 being a ligand for binding metals in hyperaccumulator species, 69 including Zn. 70 Adediran et al 71 also reported Zn−histidine complexation in roots of Vicia sativa, and this was thought to be controlled by nitrogen metabolism potentially driven by legume-associated symbiotic bacteria. This may explain why we also see it only in plant roots inoculated with R. leguminosarum.…”
Section: Resultsmentioning
confidence: 99%